The Presence, Provenance and Presentness of a Non Artifact - David Alexander Pantalony (Museum & Society, 2019)
This article is a biography of a green tile collected from a Canadian hospital. It explores various properties of the tile in order to draw out lessons for research and display in museums. There are immediate sensory qualities of the tile that have inspired an exhibit about the colour green in medicine; there are aspects of the tile's provenance that bring out multiple local and international narratives; there are stories of the tile's present context that provide a powerful reminder that museum artifacts are not just vehicles for exploring the past, but for understanding what remains in the present.